Resolving large financial intermediaries: Banks versus housing enterprises - Wall, Larry D.; Eisenbeis, Robert A.; Frame, W. Scott (Journal of Financial Stability, 2005)
This paper examines the policy issues associated with resolving the possible failure of Fannie Mae or Freddie Mac (housing enterprises). It compares and contrasts these issues with those raised in the context of large bank failures and also identifies important differences in the extant supervisory authorities. Based on these discussions, a number of policy suggestions are offered to minimize the cost of resolution and protect taxpayers from loss should a large bank or housing enterprise fail.